Analisis Struktur Persajakan Pada Puisi “Bahasa, Bangsa” Karya Mohammad Yamin - Davina Pebrimireni (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
This study aims to examine (1) the structural form of the study contained in the poem Language, Nation by Mohammad Yamin. (2) analysis of the meaning contained based on the reader's point of view. The method used in this study is a qualitative descriptive method. The data acquisition used is by reading, listening and note-taking techniques. The data of this study is sourced from the poetry verse Language, Nation by Mohammad Yamin. The data analysis technique used in this study is the content analysis technique. The results of this study show that: (1) the intrinsic form of the structure in each array of poems is in the form of rhymes or old poems based on their sentence patterns (2) the analysis of the meaning in this poem is a sense of nationalism as a form of love and concern for language and nation.